Kejadian Banjir Kilat di Daerah Yan, Kedah: Perspektif Penduduk dan Pihak Berkuasa Tempatan - Mohd Yusof , Nurul Syafini; Sarpin, Norliana; Mohamed, Sulzakimin; Shafii, Haryati; Masrom, Md. Asrul Nasid (Research in Management of Technology and Business, 2024)
The phenomenon of flash floods often occurs in Malaysia. Flash floods have had a negative effect on people in terms of safety and property destruction. Flash floods often occur due to natural combinations such as prolonged heavy rain and also the effects of human activities. This study was conducted to achieve three objectives, namely to identify the effects of flash floods on the residents of Yan, Kedah, to identify the factors that cause flash floods in Yan, Kedah.This study was conducted using a mixed method which is a quantitative method to achieve the research objective 1 and a qualitative method to achieve the research objective 2 and 3. The questionnaire was used as a data collection instrument for the quantitative method by distributing the questionnaire to 137 residents of Kampung Acheh, Yan who were involved in flash floods.This study has used a qualitative method which is interviewing Jabatan Pengairan dan Saliran, Majlis Daerah and Jabatan Kerja Raya.This study involves the area of Sungai Titi Hayun in Yan because this area of the river is the worst affected by floods.Quantitative data obtained is analyzed using descriptive analysis with the help of SPSS software,meanwhile, qualitative data from interviews is analyzed using the content analysis method.The results of this study found that among the main effects of flash floods that have been faced by the residents are the residents experiencing trauma,the spread of disease outbreaks such as cholera and malaria as well as damage to property and infrastructure. Among the causes of flash floods in Yan is the occurrence of landslides at the top of Gunung Jerai and the water head has brought soil erosion, silt and logs to the river. Next, flash floods also occur due to rivers that are not maintained regularly and also the effects of the construction of resorts,chalets and pools on the river course which has had the effect of changing the structure of the river course and blocking the flow of river water. Among the improvement suggestions to deal with the problem of flash floods in Yan,Kedah is the construction of the Sabo Dam,upgrading the drainage system and increasing flood mitigation. Therefore, this study was carried out to help find out the causes that cause flash floods and to help those responsible in dealing with this issue for the well-being of local residents.